Exhaled nitric oxide levels in non-allergic and allergic mono- or polysensitised children with asthma - Silvestri, M (BMJ Group, 2001)
BACKGROUND—Increased fractional exhaled NO concentrations (FENO) and blood/tissue eosinophilia are frequently reported in allergic children with mild asthma and are thought to reflect the intensity of the inflammation characterising the disease. The aim of this study was to investigate possible differences in FENO levels or in the intensity of the blood eosinophilia in allergic and non-allergic asthmatic children. METHODS—112 children with stable, mild, intermittent asthma with a positive bronchial challenge to methacholine were consecutively enrolled in the study; 56 were skin prick test and RAST negative (non-sensitised) while 56 were sensitised to house dust mites (23 only to house dust mites (monosensitised) and 33 were sensitised to mites and at least another class of allergens (pollens, pet danders, or moulds)). Nineteen sex and age matched healthy children formed a control group. RESULTS—Compared with non-allergic patients, allergic children had a significantly higher rate of blood eosinophilia (p=0.0001) with no differences between mono- and polysensitised individuals. Forced expiratory volume in 1 second (FEV(1)), forced vital capacity (FVC), forced expiratory flow at 25-75% of vital capacity (FEF(25-75%)), and the degree of bronchial reactivity to methacholine were similar in non-atopic and atopic children, with no differences between mono- and polysensitised individuals. FENO levels measured by chemiluminescence analyser were higher in asthmatic children (15.9(14.3) ppb) than in the control group (7.6 (1.6) ppb, p=0.04) and higher in allergic patients (23.9 (2.1) ppb) than in non-allergic patients (7.9 (0.8) ppb, p=0.0001), but there were no differences between mono- and polysensitised individuals (p>0.1). Significant correlations between blood eosinophilia and FENO levels were seen only in allergic (r=0.35, p<0.01) and in polysensitised individuals (r=0.45, p<0.05). CONCLUSIONS—In children with mild asthma, a similar degree of functional disease severity may be associated with a higher inflammatory component in allergic than in non-allergic subjects.